Endoplasmic reticulum proteins Meigo and Gp93 govern dendrite targeting by regulating Toll-6 localization. - Kamemura, K.; Moriya, H.; Ukita, Y.; Okumura, M.; Miura, M.; Chihara, T. (Developmental Biology, 2022)
Neuronal target recognition is performed by numerous cell-surface transmembrane proteins. Correct folding of these proteins occurs in the endoplasmic reticulum (ER) lumen of the neuronal cells before being transported to the plasma membrane of axons or dendrites. Disturbance in this protein folding process in the ER leads to dysfunction of neuronal cell surface molecules, resulting in abnormal neuronal targeting. In this study, we report that the ER-resident protein Meigo in Drosophila, governs the dendrite targeting of olfactory projection neurons (PNs) along the mediolateral axis of the antennal lobe by regulating Toll-6 localization. Loss of Meigo causes Toll-6 mislocalization in the PNs and mediolateral dendrite targeting defects, which are suppressed by Toll-6 overexpression. Furthermore, we found that the ER-chaperone protein, Gp93, also regulates the mediolateral targeting of PN dendrites by localization of the Toll-6 protein. Gp93 overexpression in the PN homozygous for the meigo mutation, partially rescued the dendrite targeting defect, while meigo knockdown decreased Gp93 expression levels in cultured cells. These results indicate that the ER-proteins Meigo and Gp93 regulate dendrite targeting by attenuating the amount and localization of cell surface receptors, including Toll-6, implying the unexpected but active involvement of ER proteins in neural wiring.